Demography and selection shape transcriptomic divergence in field crickets. (1st March 2018) - Blankers, Thomas; Vilaça, Sibelle T.; Waurick, Isabelle; Gray, David A.; Hennig, R. Matthias; Mazzoni, Camila J.; Mayer, Frieder; Berdan, Emma L.
Abstract: Gene flow, demography, and selection can result in similar patterns of genomic variation and disentangling their effects is key to understanding speciation. Here, we assess transcriptomic variation to unravel the evolutionary history of Gryllus rubens and Gryllus texensis, cryptic field cricket species with highly divergent mating behavior. We infer their demographic history and screen their transcriptomes for footprints of selection in the context of the inferred demography. We find strong support for a long history of bidirectional gene flow, which ceased during the late Pleistocene, and a bottleneck in G. rubens consistent with a peripatric origin of this species. Importantly, the demographic history has likely strongly shaped patterns of genetic differentiation (empirical FST distribution). Concordantly, FST ‐based selection detection uncovers a large number of outliers, likely comprising many false positives, echoing recent theoretical insights. Alternative genetic signatures of positive selection, informed by the demographic history of the sibling species, highlighted a smaller set of loci; many of these are candidates for controlling variation in mating behavior. Our results underscore the importance of demography in shaping overall patterns of genetic divergence and highlight that examining both demography and selection facilitates a more complete understanding of genetic divergence during speciation.